2014
DOI: 10.1161/circresaha.113.301954
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Four-and-a-Half LIM Domain Protein-2 Increases Survival, Migratory Capacity, and Paracrine Function of Human Early Outgrowth Cells Through Activation of the Sphingosine Kinase-1 Pathway

Abstract: Rationale: Inhibition of four-and-a-half LIM domain protein-2 (FHL2) attenuates atherosclerotic lesion formation and increases endothelial cell migration. Early outgrowth cells (EOCs) contribute substantially to endothelial repair. Objective: We investigated the role of FHL2 in the regulation of EOCs. Methods and Results: Hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…We have recently shown that FHL2 deficiency is protective, promoting early outgrowth cell function as well as endothelial cell survival and function. 18 In the present study, we demonstrate that the absence of FHL2 in myeloid and vascular cells reduces plaque development in the ApoE −/− atherosclerotic mouse model. Moreover, we provide evidence that this atheroprotective effect could be, at least in part, because of reduced adhesion molecule expression in endothelial cells and because of a change in the chemokine/chemokine receptor expression balance leading to decreased recruitment of 20 and macrophages.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We have recently shown that FHL2 deficiency is protective, promoting early outgrowth cell function as well as endothelial cell survival and function. 18 In the present study, we demonstrate that the absence of FHL2 in myeloid and vascular cells reduces plaque development in the ApoE −/− atherosclerotic mouse model. Moreover, we provide evidence that this atheroprotective effect could be, at least in part, because of reduced adhesion molecule expression in endothelial cells and because of a change in the chemokine/chemokine receptor expression balance leading to decreased recruitment of 20 and macrophages.…”
Section: Discussionsupporting
confidence: 63%
“…This result is in line with our previous data showing an improved re-endothelialization capacity in FHL2 −/− mice related to enhanced viability and migration of EC. 18 In addition, we observed a lower adhesion capacity of monocytes incubated with ApoE/FHL2 −/− ECs in a flow chamber. Hence, lower adhesive properties of ECs may well mitigate monocyte recruitment in ApoE/ FHL2 −/− mice.…”
Section: Discussionmentioning
confidence: 67%
“…CMA is a more advanced technique used to analyze the entire coding and non-coding regions of a patient’s genome for CNV mutations. Currently, CMA analysis detects approximately 70% of CNV mutations (62). WES is the most comprehensive test currently available.…”
Section: Genetic Testing In Chd Patientsmentioning
confidence: 99%
“…It evaluates a patient’s entire exome for point mutations and sometimes CNV mutations (not all testing protocols include CNV analysis). WES may miss up to 5% of specific gene mutations, but its sensitivity continues to improve with time (62). …”
Section: Genetic Testing In Chd Patientsmentioning
confidence: 99%
“…FHL2 can function as adaptors to mediate protein-protein interactions because of the LIM domain. Besides, FHL2 shuttles between cytosol and nucleus, and plays important roles in the regulation of signal transduction [912], cell survival [13, 14], motility [15, 16] and adhesion [17, 18]. Interestingly, FHL2 is upregulated in many cancers compared with normal tissues, for example, human melanoma, breast cancer and pancreatic cancer [11, 19, 20].…”
Section: Introductionmentioning
confidence: 99%